Psychometric assessment of the Internet Gaming Disorder diagnostic criteria: An Item Response Theory study. (December 2018) - Schivinski, Bruno; Brzozowska-Woś, Magdalena; Buchanan, Erin M.; Griffiths, Mark D.; Pontes, Halley M.
Abstract: Internet Gaming Disorder (IGD) has been recognized by the American Psychiatric Association (APA) as a tentative disorder in the latest fifth revision of the Diagnostic and Statistical Manual of Mental Disorders (DSM-5). In order to advance research on IGD, the APA has suggested that further research on the nine IGD criteria to investigate its clinical and empirical feasibility is necessary. The aim of the present study was to develop the Polish the Internet Gaming Disorder Scale–Short-Form (IGDS9-SF) and scrutinize the nine IGD criteria empirically. To achieve this, the newly developed IGDS9-SF was examined using a wide range of psychometric methods, including a polytomous Item Response Theory (IRT) analysis to evaluate the measurement performance of the nine IGD criteria. A sample of 3377 gamers (82.7% male, mean age 20 years, SD = 4.3 years) was recruited online for the present study. Overall, the findings obtained confirmed that suitability of the Polish IGDS9-SF to assess IGD amongst Polish gamers given the adequate levels of validity and reliability found. The IRT analysis revealed that the IGDS9-SF is a suitable tool to measure IGD levels above the average; however, criteria "continuation" (item 6), "deception" (item 7), and "escape" (item 8) presented with poor fit. Taken together, these results suggest that some of the diagnostic criteria may present with a different clinical weighting towards final diagnosis of IGD. The implications of these findings are further discussed. Highlights: The APA diagnostic criteria for IGD was investigated in a large sample of gamers. The construct of IGD was examined via validity analysis and Item Response Theory. The results revealed the suitability of the IGDS9-SF to assess IGD-related symptoms. Each IGD criterion present with distinct clinical diagnostic weighting. The nine IGD criteria need to take into account different clinical weighting.